Contemporary civil litigation - Yeazell, Stephen C (Aspen Publishers, 2009)
Includes bibliographical references.; Lawyers, clients, and civil litigation -- Financing litigation, financing law : basic mechanisms -- Settlement : the law and strategy of litigation risk control -- Judges.